An Intersemiotic Translation of a Mobile Art Project to a Photographic Essay. (2nd January 2016) - Vitral, Letícia Alves; Aguiar, Daniella; Queiroz, João
Abstract : VIA is a mobile art project (video-dance and computational music) semiotically translated to photographic media by means of formal constraints derived from selected properties of Rio de Janeiro's predefined downtown routes. Under the constraints of street buildings and the morphology of the routes, questions regarding the influence of the bodily movements of the urban space led to the creation of a dance typology. This typology is related to pedestrians in the area and to the structure of the buildings spans where the performance happened. The dance movements captured in the videos were restricted and regulated by the physical environment and its main features. Here, an intersemiotic translation of a mobile art project to a photographic essay is presented and described. It strongly relates, and tentatively explores, both an artistic research praxis and a theoretical discussion. The essay explores an analogous semiotic effect from the VIA project on the photographic essay as a result of this investigation.